A contribution of beef to human health : a review of the role of the animal production systems - Pighin, Darío Gabriel (2016)
Meat and meat products constitute important source of protein, fat, and several functional compounds. Although beef consumption may implicate possible negative impacts on human health, its consumption can also contribute to human health. Quality traits of beef, as well as its nutritional properties, depend on animal genetics, feeding, livestock practices, and post mortem procedures. Available data show that emerging beef production systems are able to improve both, quality and nutritional traits of beef in a sustainable way. In this context, Argentina’s actions are aimed at maximising beef beneficial effects and minimising its negative impact on human health, in a way of contributing to global food security.